Pengaruh Viral Marketing, Brand Image, dan e-WOM terhadap Minat Beli Produk Somethinc pada Followers Instagram @somethincofficial - Ananda Nabilaturrahmah; Salim Siregar (Peneliti.net, 2022)
This research was conducted to analyze to provide knowledge and explanations about consumer buying interest in SomeThinc products through viral marketing, brand image, and e-wom. Quantitative methods with verification and descriptive approaches are the methods used in this research. Data were collected using questionnaires and library studies with the object of research being Instagram followers @somethincofiicial with a total of 400 respondents. Path analysis using a range of scales is an analytical tool contained in this study. The results showed that viral marketing on buying interest was in very good criteria, while brand image and e-wom on buying interest were in good criteria. In the results of the t-test, it can be explained that the significant value of viral marketing is (0.000) < (0.05), brand image (0.000) < (0.05), and e-wom (0.013) < (0.05) which can mean that viral marketing, brand image, and e-wom have a positive and significant influence on buying interest. Then there is a simultaneous influence between viral marketing, brand image, and e-wom on buying interest by 69.4% and the remaining 30.6% from other factors not examined in this study.